2022
DOI: 10.3389/fphar.2022.899198
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Hyper-Inflammation as Major Drivers of Severe COVID-19 and Long COVID: Implications for the Benefit of High-Dose Intravenous Vitamin C

Abstract: Oxidative stress is a pivotal point in the pathophysiology of COVID-19 and presumably also in Long-COVID. Inflammation and oxidative stress are mutually reinforcing each other, thus contributing to the systemic hyperinflammatory state and coagulopathy which are cardinal pathological mechanisms of severe stages. COVID-19 patients, like other critically ill patients e.g. with pneumonia, very often show severe deficiency of the antioxidant vitamin C. So far, it has not been investigated how long this deficiency l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 117 publications
1
59
0
4
Order By: Relevance
“…It is still premature to confirm whether or not lung involvement or signs of ongoing heart inflammation occur as a temporary response to COVID-19 infection and will spontaneously be resolved over time and whether COVID-19 affects other inflammation-related complications or basic diseases, such as intestinal diseases [ 14 , 15 , 16 , 17 ]. Oxidative stress may also play an important role in the development of symptoms from Long COVID [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is still premature to confirm whether or not lung involvement or signs of ongoing heart inflammation occur as a temporary response to COVID-19 infection and will spontaneously be resolved over time and whether COVID-19 affects other inflammation-related complications or basic diseases, such as intestinal diseases [ 14 , 15 , 16 , 17 ]. Oxidative stress may also play an important role in the development of symptoms from Long COVID [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data and other reported evidence suggest that SARS-CoV-2 PLpro/NSP3 may be a highly attractive and druggable target not only in acute COVID-19 but also in long-COVID [ 41 , 42 ]. Moreover, several lines of evidence demonstrated that inflammation and oxidative stress mutually reinforce each other in COVID-19 and presumably also in long-COVID, highlighting the major role of oxidative unbalance as a trigger of both acute and chronic inflammation [ 27 , 43 ]. Therefore, it is plausible that natural antioxidant molecules may counteract SARS-CoV-2 redox status derangement and consequent inflammation representing a possible therapy for improving signs and symptoms of long-COVID syndrome [ 26 , 27 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…HXT is a phenolic compound found in the leaves and fruits of olive with antioxidant, anti-inflammatory and antimicrobial activities [ 20 , 21 ]. The antiviral activity of olive leaf metabolites against SARS-CoV-2 was reported in several in silico computational studies [ 43 , 44 ]. In particular, Yu et al tested several viral targets, such as viral proteases (Mpro/3CLpro, PLpro), TLRs, ACE2, RBD, NSP15, HSPA5 SBDβ, TMPRSS2, S protein and furin [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brown module was responsible for the immune responses of various cytokines, which might play an important role in the progression and prognosis of patients [53] , [54] . The grey module plays a vital role in oxygen transport and oxidative stress, the latter is an important part of the pathogenesis of COVID-19 [55] and interacts with the patients’ inflammatory response [56] . In addition, through PPI network analysis, we found that most of the identified hub genes were involved in MCODEs related to the cell invasion process induced by viruses, indicating the significant role of these genes in responding to virus infection.…”
Section: Discussionmentioning
confidence: 99%